Current advances on the microbiome and role of probiotics in upper airways disease. Issue 1 (February 2020) - Yamanishi, Shingo; Pawankar, Ruby
Abstract : Purpose of review: The prevalence of chronic upper airway inflammatory diseases such as allergic rhinitis and chronic rhinosinusitis (CRS) is increasing markedly posing a potential health threat globally. The involvement of the upper respiratory microbiota in chronic inflammatory diseases of the upper airways has been of considerable interest. The purpose of this review is to understand the characteristics of upper respiratory microbiota in both healthy and chronic inflammatory diseases of the upper airways like allergic rhinitis and CRS and to know the potential role of interventions with probiotics. Recent findings: We present here the studies on the nasal microbiota in healthy infants, allergic rhinitis, and CRS. The results demonstrate that there are stable and unstable profiles of microbiota during infancy. Decreased diversity or an imbalance of the microbial composition could be an important factor in the development of both allergic rhinitis and CRS. We also discuss here several recent animal and human studies that demonstrate the effect of probiotics in allergic rhinitis and chronic rhinosinusitis. Results from human studies (clinical trials) have demonstrated that probiotics may be effective for allergic rhinitis, but there are no consistent results in human CRS trials. Summary: Several strains of probiotics revealed potential efficacy for allergic rhinitis but not for CRS. Large clinical trials are essential to establish robust data on probiotics for chronic inflammatory upper airways diseases like allergic rhinitis and CRS.